'Something is better than nothing': Early childhood caregiver‐child music classes taught remotely in the time of COVID-19. (1st December 2020) - Koops, Lisa Huisman; Webber, Samantha C.
Many early childhood music teachers suddenly shifted to remote teaching in March 2020 due to the COVID-19 pandemic. The purpose of this intrinsic case study was to gather information about parents' and caregivers' perspectives on and reactions to remote teaching of caregiver‐child early childhood music classes. The participant families were enrolled in an on-site music class when the switch in format happened due to COVID-19 and were given the option of continuing with instruction via Zoom or receiving a refund for the remainder of the semester. All families were invited to complete a survey with questions about their decision to participate or not and suggestions for ongoing remote programming. Families who chose to participate in synchronous online classes were invited to complete interviews. Eleven adults, representing nine enrolled children, offered their perceptions of the affordances and constraints of the remote caregiver‐child music class and suggestions for improvement of remote teaching. Four themes arose in the interviews: (1) the centrality of interaction, (2) the need to support families, (3) the kids & screens paradox and (4) something is better than nothing. Families who chose not to do remote classes in the spring reported they were not interested in trying Zoom classes in the fall either. The main reason families gave for not wanting to participate was concerns about children and screen time. We share implications for teaching and suggestions for future research.